Evaluation of common variants in the six known maturity-onset diabetes of the young (MODY) genes for association with type 2 diabetes. - Winckler, W; Weedon, M; Graham, R; McCarroll, SA; Purcell, S; Almgren, P; Tuomi, T; Gaudet, D; Boström, K; Walker, M; Hitman, G; Hattersley, A; et al. (2007)
An important question in human genetics is the extent to which genes causing monogenic forms of disease harbor common variants that may contribute to the more typical form of that disease. We aimed to comprehensively evaluate the extent to which common variation in the six known maturity-onset diabetes of the young (MODY) genes, which cause a monogenic form of type 2 diabetes, is associated with type 2 diabetes. Specifically, we determined patterns of common sequence variation in the genes encoding Gck, Ipf1, Tcf2, and NeuroD1 (MODY2 and MODY4-MODY6, respectively), selected a comprehensive set of 107 tag single nucleotide polymorphisms (SNPs) that captured common variation, and genotyped each in 4,206 patients and control subjects from Sweden, Finland, and Canada (including family-based studies and unrelated case-control subjects). All SNPs with a nominal P value <0.1 for association to type 2 diabetes in this initial screen were then genotyped in an additional 4,470 subjects from North America and Poland. Of 30 nominally significant SNPs from the initial sample, 8 achieved consistent results in the replication sample. We found the strongest effect at rs757210 in intron 2 of TCF2, with corrected P values <0.01 for an odds ratio (OR) of 1.13. This association was observed again in an independent sample of 5,891 unrelated case and control subjects and 500 families from the U.K., for an overall OR of 1.12 and a P value <10(-6) in >15,000 samples. We combined these results with our previous studies on HNF4alpha and TCF1 and explicitly tested for gene-gene interactions among these variants and with several known type 2 diabetes susceptibility loci, and we found no genetic interactions between these six genes. We conclude that although rare variants in these six genes explain most cases of MODY, common variants in these same genes contribute very modestly, if at all, to the common form of type 2 diabetes.